A silent "shipyard eye": lessons from an epidemic keratoconjunctivitis outbreak in Portugal. (30th September 2020) - Moreira, A; Abreu Gomes, F; Mouro, M; Lopes, D; Bragança Pereira, M; Duarte, S; Cunha, I; Machado Gil, M; Calado, J
Abstract: Issue: Adenoviral conjunctivitis is the most common cause of conjunctivitis. Its most severe form is epidemic keratoconjunctivitis (EKC). This highly contagious disease is the only form to significantly involve the cornea and may cause visual impairing sequelae that persist for years. Description: On January 2020, staff members at a childcare facility (CCF) alerted the Public Health Unit of Loures-Odivelas to a suspected conjunctivitis outbreak. The CCF was responsible for 57 children, separated in different rooms: a nursery (4-12 months), a pre-school (1-3 years) and a kindergarten (4-5 years). At the initial assessment, 4 cases of active disease were identified, all of which were at home and under treatment. CCF staff had previously identified 33 cases. Symptom onset of the index case had occurred more than 5 weeks before the alert. Infection control and epidemiological investigation were initiated. CCF staff was instructed to implement preventive measures, including careful disinfection of surfaces and toys, as well as frequent handwashing. Information about the disease and recommendations were sent to the children's caretakers. Results: A total of 87 cases distributed in 8 weeks were identified: 28 at the CCF (25 children and 3 workers) and 59 close contacts (50 adults and 9 children). Average duration of disease was 14.1 days. In total, 43.9% of the children attending the CFF were affected. The highest attack rate was observed at the pre-school (69.2%, against 38.9% and 17.6% at the nursery and the kindergarten, respectively). 88.0% of the CCF children's households were affected. The average number of affected close contacts per affected child attending the CCF was 2.63. Corneal involvement was observed in 17, 4% of cases. Lessons: EKC outbreaks may go unnoticed by public health services, despite its high contagiousness and impact. Improvement of communication with organizations in the community is essential to secure future early detection and intervention. Key messages: Epidemic keratoconjunctivitis is a highly contagious disease with potential long-term consequences. Early detection and intervention by public health services are essential to mitigate the impact of outbreaks and depend on well-established communication lines with institutions in the community.